Effect of metakaolin pozzolanic activity in the early stages of cement type II paste and mortar hydration - Cherem Da Cunha, A. L.; Gonçalves, J. P.; Büchler, P. M. [UNESP]; Dweck, J. (Springer Nature, 2008)
The cement industry is one which most emits polluting gases to the environment, due to the calcium carbonate calcination, as well as to the burning of fossil fuels during the manufacturing process. Metakaolin (MK), in partial substitution to cement in its applications, is having a special worldwide growing role, for the technological increment due to its pozzolanic activity and mainly to the reduction of those emissions. In the present paper, the effect of pozzolanic activity of metakaolin was analyzed by thermal analysis in pastes and mortars of type II Portland cement in the first three days of the hydration, during which, relevant initial stages of the hydration process occur. By non-conventional differential thermal analysis (NCDTA), paste and mortar samples containing 0, 10, 20, 30 and 40% of metakaolin in cement mass substitution and using a 0.5 water/(total solids) mass ratio, were evaluated. The NCDTA curves, after normalization on cement mass basis and considering the heat capacity of each reactant, indicate that the pozzolanic activity behavior of metakaolin is different in pastes and mortars. Through the deconvolution of the normalized NCDTA curve peaks, it can be seen that ettringuite formation increases as cement substitution degree (CSD) increases, in both cases. Tobermorite formation is more enhanced in mortars than in pastes by MK, with a maximum formation at 30% of CSD. In the pastes, tobermorite formation increases as CSD increases but it is practically the same at 30 and 40% of CSD. © 2008 Springer Science+Business Media, LLC.
Keywords: Cement; Metakaolin; Mortars; NCDTA; Pastes; Pozzolanic activity